2019
DOI: 10.3390/jcm8050597
|View full text |Cite
|
Sign up to set email alerts
|

Research Evidence on High-Fat Diet-Induced Prostate Cancer Development and Progression

Abstract: Although recent evidence has suggested that a high-fat diet (HFD) plays an important role in prostate carcinogenesis, the underlying mechanisms have largely remained unknown. This review thus summarizes previous preclinical studies that have used prostate cancer cells and animal models to assess the impact of dietary fat on prostate cancer development and progression. Large variations in the previous studies were found during the selection of preclinical models and types of dietary intervention. Subcutaneous h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 90 publications
0
40
0
8
Order By: Relevance
“…Dietary fat not only promotes obesity, but also PCa progression and disease aggressiveness. Several preclinical PCa studies have compared high-fat (or Western-style diets) versus low fat diet and reported that the former promotes AKT and ERK activity, tumor growth, tumor incidence in genetically engineered/transgenic mouse models, tumor progression to CRPC and metastasis (reviewed in Narita et al, 2019 ). Clinical case-control studies indicated saturated fat is associated with an increased risk of advanced PCa ( Bairati et al, 1998 ; Stéfani et al, 2000 ; Slattery et al, 1990 ; Whittemore et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat not only promotes obesity, but also PCa progression and disease aggressiveness. Several preclinical PCa studies have compared high-fat (or Western-style diets) versus low fat diet and reported that the former promotes AKT and ERK activity, tumor growth, tumor incidence in genetically engineered/transgenic mouse models, tumor progression to CRPC and metastasis (reviewed in Narita et al, 2019 ). Clinical case-control studies indicated saturated fat is associated with an increased risk of advanced PCa ( Bairati et al, 1998 ; Stéfani et al, 2000 ; Slattery et al, 1990 ; Whittemore et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggested that a high-fat diet plays a critical role in the development of PCa (Ferro et al, 2017;Narita et al, 2019). Further findings indicated deregulated lipid metabolism was positively associated with advanced PCa.…”
Section: Discussionmentioning
confidence: 97%
“…Z kolei czynnikami o właściwościach protekcyjnych, oprócz zwiększonej aktywności fizycznej, są spożywanie dużych ilości ryb i warzyw, zwłaszcza pomidorów [29]. Badania sugerują, że ilość tłuszczu w diecie wpływa nie tylko na rozwój, ale też na stopień agresywności raka stercza [30].…”
Section: Styl żYcia Otyłość I Zespół Metaboliczny Jako Czynniki Etiounclassified
“…Duża prospektywna analiza wykazała, że wyższe stężenia peptydu C w surowicy były ściśle związane ze zwiększoną śmiertelnością u chorych z rakiem stercza [41], a wysoki poziom insuliny oraz aktywacja osi insulina i IGF-1/IGF-1R poprzez sygnalizację kinazy tyrozynowej zwiększały progresję raka. Pobudzenie receptorów kinazy tyrozynowej skutkuje aktywacją kaskady białek wewnątrzkomórkowych i zmianą ekspresji genów syntezy białek [30].…”
Section: Styl żYcia Otyłość I Zespół Metaboliczny Jako Czynniki Etiounclassified